Services in the Trans-Pacific Partnership : What Would Be Lost? - Gootiiz, Batshur (World Bank, Washington, DC, 2017)
As the fate of the Trans-Pacific Partnership (TPP) hangs in balance, an evaluation of what it offers could inform current decisions and shape future negotiations. The TPP's services component has been hailed as one of the agreement's major accomplishments. To assess the agreement’s impact on national policy in the major services sectors, we created a new public database. This database reveals that TPP commitments seldom go beyond countries' applied policies, suggesting the explicit liberalization resulting from the agreement is limited only to a few countries and a few areas. However, the TPP enhances transparency and policy certainty because parties' services commitments cover more trading partners, more sectors and are in some cases closer to applied policies than their commitments under previous agreements. Furthermore, new TPP rules, including on state-owned enterprises, government procurement and competition policy, could enhance services market access. In particular, the TPP breaks new ground in prohibiting restrictions on international data flows, while at the same time creating unprecedented obligations on all parties to protect consumers from fraud and protect privacy. These dual obligations on importing and exporting countries represent a model for regulatory cooperation that could elicit greater market opening if applied to other areas.